Studi Efektifitas Pembiayaan Itervensi Model Adaptasi Berbasis Pemberdayaan Keluarga Untuk Meningkatkan Kualitas Hidup Pasca Stroke - Dharma, Kelana Kusuma; Parellangi, Andi; Rahayu, Halina (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2020)
Objective: The purpose of this study was to analyze the cost-effectiveness ratio of the caregiver empowermentprogram based on the adaptation model in improving the functional capacity and quality of life post-strokecompared to hospital rehabilitation programs.Methods: This study was a quasi-experimental study with a pre-test and post-test control group design.Researchers divided the selected sample into 2 groups: an intervention group that received CEP-BAM and acontrol group that received a hospital rehabilitation program. The sampling method used was stratifiedrandom sampling. A sample of 56 people (28 people per group) was calculated based on the sample sizeformula for the hypothesis of the two independent group means.Results: There were no significant differences in functional capacity and quality of life after a stroke beforeand after treatment between the two groups. There was a significant increase in functional capacity and qualityof life after treatment in each group (p = 0.001). The cost-effectiveness ratio showed the need for funding of Rp564,634 to improve 1 value of quality of life using CEP-BAM and Rp 566,527 using the hospital rehabilitationprograms.Conclusion: CEP-BAM interventions and hospital rehabilitation programs showed the same cost-effectivenessin increasing the functional capacity and the quality of life after stroke. Recommendation: CEP-BAM can be used in the post-stroke rehabilitation program, especially in areas that donot have rehabilitation unit facilities.